Servant Leadership and Followers Prosocial Rule-Breaking: The Mediating Role of Public Service Motivation - Khan, Naqib Ullah; Zada, Muhammad; Ullah, Asad; Khattak, Afraseyab; Han, Heesup; Ariza-Montes, Antonio; Araya-Castilo, Luis (Frontiers in Psychology, 2022)
This research explores the effect of servant leadership on prosocial rule-breaking and the mediating mechanism of public service motivation between the association of servant leadership and prosocial rule-breaking. The said phenomenon is examined in the civil service context of Pakistan during the continuing crises of the Covid-19 pandemic, a situation where the traditional civil service policy and rule system has become highly complicated for passionate employees service performance and efficiency, and where servant leadership has received greater attention for inspiring the attitudinal and behavioral outcomes of frontline workers during the pandemic. Data were collected from 546 frontline workers of the corona relief tiger force. The findings of the study reveal that servant leadership has a significant effect on prosocial rule-breaking and public service motivation, and that public service motivation significantly promotes prosocial rule-breaking. The results also reveal that servant leadership has a significant impact on prosocial rule-breaking via engendering public service motivation.